Axonal fasciculation and the role of polysialic acid‐neural cell adhesion molecule in rat cortical neurons. Issue 11 (21st August 2013) - Wakade, Chandramohan G.; Mehta, Shyamal H.; Maeda, Manebu; Webb, R. Clinton; Chiu, Fung‐Chow
<x xml:space="preserve">Abstract</x> Axonal fasciculation is a mechanism deployed by growing axons to reach their targets during development of the nervous system. Published data have suggested the involvement of neuronal cell adhesion molecules (NCAM) in axonal fasciculation. We have characterized the formation of axonal fascicles in serum‐free, primary cultures of cortical neurons from embryonic rat brains. Unlike the published data, axonal fascicles in our system have a unique morphology: they are waveform, are rarely thicker than 20 μm, and can reach up to several millimeters in length. We observed an age and time dependence in the formation of fascicles. They formed only in cultures from embryonic day 15–17 brain and only between 4 days in vitro (DIV) and 11 DIV. Electron microscopy showed that the fascicles consisted of mostly axonal processes. Immunocytochemical staining confirmed that the fascicles were positive for the 66‐kDa neurofilament protein, NF66, but they contained few, if any, microtubule‐associated protein‐2‐positive or glial fibrillary acidic protein‐positive processes. Polysialic acids appeared to be critical in the formation of fascicles. Neuraminidase treatment prevented the formation of fascicles when added before 5 DIV. Addition of a specific inhibitor blocked the effect of neuraminidase. The cortical neurons in our model shared several important features with axon fasciculation in vivo and may provide a unique system for studying the molecular mechanisms involved in the formation of axonal tracts in the brain. © 2013 Wiley Periodicals, Inc.